Actualizing the venturing model in Ukraine - Yereshko, Julia; Kreidych, Iryna; Kravchenko, Maryna; Kazak, Oksana; Kharchenko, Оleksandr (Business: Theory and Practice, 2024)
The financing of innovations is the driving driver of the innovative model of development of any country, and Ukraine in particular. In modern conditions, the importance of venture capital for the economy of Ukraine is growing against the background of reducing alternatives to raising capital for the development of small and high-tech businesses. The reasons for the current state of decline in the innovation and investment process in Ukraine are analyzed and identified. Peculiarities of venture investment in Ukraine are studied. It is determined that the vast majority of venture capital institutions, regardless of their field of activity, are used mainly by large industrial and financial groups to preserve assets and minimize taxation, rather than to finance innovation. The obtained results give grounds for the conclusion that the essence of venture entrepreneurship in Ukraine does not correspond to the American and European models. The current conditions turn venture funds in Ukraine from an instrument of innovative development into a means of making a profit for large financial and industrial groups, which is a hidden reason for slowing down the innovation and investment process. An updated Ukrainian venture model is proposed, taking into account the peculiarities of the economy and a thorough rethinking of the existing structure of venture capital. The introduction of a rational combination of public, private, and research components of the investment process is proposed, i.e. the need to involve universities, scientists, and the scientific elite in the venture industry. It is determined that this model is only one of the components of a comprehensive program to stimulate investment demand, which also includes: ensuring macroeconomic stability; ensuring economic freedom; ensuring economic security; an increase of investment resource; impact on investment propensity; liberalization and development of the financial market; stimulating investment activities through the mechanism of state support for business and science partnerships.